Simultaneous determination of tocopherols, carotenoids and phytosterols in edible vegetable oil by ultrasound-assisted saponification, LLE and LC-MS/MS. (15th August 2019) - Zhang, Liangxiao; Wang, Sujun; Yang, Ruinan; Mao, Jin; Jiang, Jun; Wang, Xiupin; Zhang, Wen; Zhang, Qi; Li, Peiwu
Highlights: Ultrasound-assisted saponification and LLE were used to extract targets from oil. Conditions of saponification were optimized by using central composite design. Simultaneous determination of tocopherols, carotenoids and phytosterols were proposed. Abstract: A method was developed to simultaneously determine eight bioactive compounds in edible oil based on ultrasound-assisted saponification, liquid-liquid extraction and liquid chromatography coupled with tandem mass spectrometry. Central composite design was employed to optimize ultrasonic temperature and time of saponification. Sample treatment was conducted by ultrasound-assisted saponification at temperature of 75 °C for 40 min. Limits of detection and limits of quantification ranged from 2.0 to 3.2 and from 6.1 to 10.0 ng/mL, respectively. Linear correlations were obtained (R 2  > 0.99) and the recoveries at three spiked levels were between 81.7% and 112.0%. This method was employed to determine eight compounds in camellia oils and olive oils. As results, the contents of stigmasterol, δ-tocopherol, γ-tocopherol, β-carotene and lutein in camellia oils were significantly higher than those in olive oils (p < 0.05). The proposed method can be successfully used to determination of these eight active compounds in camellia oil and other edible oils.